Medical student wellness in Canada: time for a national curriculum framework - Bourcier, Dax; Far, Rena; King, Lucas B; Cai, George; Mader, Joanna; Xiao, Maggie ZX; Simon, Christopher; McFadden, Taylor; Flynn, Leslie (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2021)
There is substantial evidence showing that medical student wellness is a worsening problem in Canada. It is apparent that medical students’ wellness deteriorates throughout their training. Medical schools and their governing bodies are responding by integrating wellness into competency frameworks and accreditation standards through a combination of system- and individual-level approaches. System-level strategies that consider how policies, medical culture, and the “hidden curriculum” impact student wellness, are essential for reducing burnout prevalence and achieving optimal wellness outcomes. Individual-level initiatives such as wellness programming are widespread and more commonly used. These are often didactic, placing the onus on the student without addressing the learning environment. Despite significant progress, there is little programming consistency across schools or training levels. There is no wellness curriculum framework for Canadian undergraduate medical education that aligns with residency competencies. Creating such a framework would help align individual- and system-level initiatives and smooth the transition from medical school to residency. The framework would organize goals within relevant wellness domains, allow for local adaptability, consider basic learner needs, and be learner-informed. Physicians whose wellness has been supported throughout their training will positively contribute to the quality of patient care, work environments, and in sustaining a healthy Canadian population.